Option for the poor and for the earth: from Leo XIII to Pope Francis - Dorr, Donal (Orbis Books, 2016)
This revised and expanded edition of a text long recognized as a classic focuses on Catholic social teaching and economic equality. Throughout, Dorr appreciates the decided strengths of Catholic social teaching but is also ready to point out its inconsistencies and weaknesses. In addition to his authoritative treatments of church documents from the century and a half of Catholic social teaching that began with Rerum Novarum in 1870, Dorr presents his magisterial take on Pope Francis' apostolic exhortation, Evangelii Gaudium, and the new encyclical on ecology, Laudato Si'. (Publisher)